2012
DOI: 10.1007/s00125-012-2490-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control is improved by 7 days of aerobic exercise training in patients with type 2 diabetes

Abstract: Aims/hypothesis Cardiovascular events and death are better predicted by postprandial glucose (PPG) than by fasting blood glucose or HbA1c. While chronic exercise reduces HbA1c in patients with type 2 diabetes, short-term exercise improves measures of insulin sensitivity but does not consistently alter responses to the OGTT. The purpose of this study was to determine whether short-term exercise training improves PPG and glycaemic control in free-living patients with type 2 diabetes, independently of the changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 43 publications
(57 reference statements)
4
67
1
1
Order By: Relevance
“…Because lifestyle factors are prominent in the etiology of T2D, efforts to combat the disease have often focused on exercise and dietary intervention [3]. One dietary intervention with plausible preventive or therapeutic potential is consumption of alcoholic beverages.…”
Section: Introductionmentioning
confidence: 99%
“…Because lifestyle factors are prominent in the etiology of T2D, efforts to combat the disease have often focused on exercise and dietary intervention [3]. One dietary intervention with plausible preventive or therapeutic potential is consumption of alcoholic beverages.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Mikus et al stated that short-term daily exercise reduces post prandial plasma glucose (PPG) and glycemia variability in Type 2 diabetes patients. [16] In the present study, blood glucose levels fasting plasma sugar (FPG) and PPG were controlled significantly in physical exercise, walking groups after exposing to physical therapy [ Table 3]. Boulé et al found intense of exercise showed remarkable improvements in blood glucose and reductions in HbA1c.…”
Section: Discussionmentioning
confidence: 63%
“…La evidencia encontrada en este trabajo muestra la relación que existe entre el entrenamiento y el mantenimiento de los niveles de glucosa a las cuatro semanas. El hecho que la actividad física disminuya los niveles glucosa sanguínea en las ratas experimentales muestra evidencia de los beneficios que aporta la actividad física per se (Shafrir et al 1999) y posiblemente puede ser una medida recomendada para regular los niveles de glucemia, que ya se sugiere en los pacientes diabéticos (Mikus et al 2012). Mayor investigación es necesaria para determinar los beneficios de un protocolo de entrenamiento, por ejemplo, prolongar el tiempo de entrenamiento y homogeneizar los grupos de estudio, asimismo medir el consumo de oxígeno y las algunas de las miokinas involucradas antes y después del entrenamiento.…”
Section: Discusión Y Conclusionesunclassified